Schizoanalysis and collaborative critical research - ERIKA BIDDLE (University of Ottawa, 2010)
For researchers working within a critique of capitalism and its relation to knowledge production, it is problematic to use traditional research methodologies endemic to the very system being critiqued unless they are somehow altered. This article investigates the potential of schizoanalysis to provide conceptual tools for such an approach. Developed through the collaborative work of Deleuze and Guattari, schizoanalysis operates from the organic principle that knowledge is an indivisible part of the way we live in the world. However, schizoanalysis is not a research methodology; it inserts itself into research methodologies, warpsthem, and reproduces itself through them.